The Pyscho-Spiritual Therapy On Mental Illness; An Islamic Approach - Ridwan Haris (Prophetic guidance and counseling journal, 2021)
Islamic therapy has developed since ancient since thedays of the Prophetpbuhandcontinued tobe practiced until now evenwith thetraditional equipments. The purpose of this study is to explore the extent of Islamic psycho-spiritual therapy for mental illness i.e. juvenile delinquency. This mental crisis generally found as a teenager problem who seeking self-identity in unfavourable environment. Typically teens often unable to manage emotions and thoughts so they mostly fell into a situation that is contrary with moral standard in the society. This paper uses qualitative method with case study to three teenage girls who undergo process of Islamic psycho-spiritual therapy. The findings shown that they get enlighten mind, self-awareness and reflections, and self-confidence and persistence domains after go through a period of recovery process. Some aspects of psycho-spiritual are also discussed in this study.AbstrakTerapi Islam telah berkembang sejak zaman Rasulullah SAW kemudian dipraktekkan sampai sekarang, bahkan dengan pendekatan yang tradisonal. Tujuan dari penelitian ini adalah untuk mengeksplorasi sejauh mana terapi psiko-spiritual Islami untuk penyakit jiwa yaitu kenakalan remaja. Krisis mental ini umumnya ditemukan pada masalah remaja yang mencari identitas diri di lingkungan yang kurang menguntungkan. Biasanya remaja seringkali tidak mampu mengelola emosi dan pikirannya sehingga kebanyakan terjerumus ke dalam situasi yang bertentangan dengan standar moral di masyarakat. Tulisan ini menggunakan metode kualitatif dengan studi kasus pada tiga remaja putri yang menjalani proses terapi psiko-spiritual Islami. Temuan menunjukkan bahwa mereka mendapatkan domain pencerahan pemikiran, kesadaran diri dan refleksi, serta kepercayaan diri dan domain ketekunan setelah melalui masa proses pemulihan. Beberapa aspek psiko-spiritual juga dibahas dalam penelitian ini